Work Stress and Compensation on Employee Turnover Intention: The Mediating Role of Work Motivation in a Regional Development Bank - Adinda Irena Rianti; M.Ali Iqbal (International Journal Business and Entrepreneurship, 2026)
High employee turnover intention poses a significant threat to the operational continuity of regional development banks, particularly during periods of organisational transformation. This quantitative study investigates the effects of work stress and compensation on employee turnover intention at PT Bank DKI—a government-owned regional bank headquartered in Jakarta, Indonesia—with work motivation as a mediating variable. Drawing on the Job Demands–Resources (JD-R) model and Goal Setting Theory, a structural model was tested using Partial Least Squares Structural Equation Modelling (PLS-SEM) and a simple random sample of 119 employees drawn from a population of 168. Measurement quality was confirmed through convergent validity (outer loadings > 0.665), composite reliability (ρ_c > 0.882), AVE > 0.599, and HTMT < 0.93 with all bootstrap confidence intervals below 1.00. The structural model explains 72.5% of variance in turnover intention and 76.7% in work motivation (R² = 0.725 and 0.767, respectively; SRMR = 0.074). All seven hypotheses were supported: work stress exerts a significant positive effect on turnover intention (β = 0.443, p < 0.001), while compensation exerts a significant negative effect (β = −0.251, p = 0.001). Work stress negatively predicts work motivation (β = −0.597, p < 0.001), whereas compensation positively predicts it (β = 0.361, p < 0.001). Work motivation, in turn, significantly reduces turnover intention (β = −0.238, p = 0.021) and fully mediates the paths from work stress (β = 0.142, p = 0.031) and compensation (β = −0.086, p = 0.026) to turnover intention. Theoretical and practical implications for human resource management in the banking sector are discussed.